Distribution and impact of the native South African wasp, Megastigmus transvaalensis (Hussey, 1956) (Hymenoptera: Torymidae) on the invasive Schinus terebinthifolia Raddi (Anacardiaceae) in South Africa - Magengelele, Nwabisa; Martin, Grant (African Entomology, 2023)
Schinus terebinthifolia Raddi (Anacardiaceae) (Brazilian pepper tree) is a tree native to subtropical South America that was introduced into South Africa as an ornamental plant. Globally, it is regarded as one of the world’s worst invasive trees. In South Africa the tree has acquired a native seed-feeding wasp, Megastigmus transvaalensis (Hussey, 1956) (Hymenoptera: Torymidae). The wasp’s native hosts are from the Searsia F.A. Barkley genus (Anacardiaceae), but it has expanded its host range to form a new association with both S. terebinthifolia and its close relative Schinus molle L. (Anacardiaceae). In order to quantify the seed predation by M. transvaalensis on S. terebinthifolia seeds, tree populations were surveyed across the Eastern Cape and KwaZulu-Natal provinces. The wasp was present at 99% of the S. terebinthifolia populations with an average of 22% of the seeds being destroyed. In the Eastern Cape province, the highest seed damage occurred at the start of the winter months, when about 35% of seeds were damaged. This fell to less than 12% in spring and summer when the plants were flowering. Megastigmus transvaalensis was found at nearly all the S. terebinthifolia populations in South Africa, but due to the limited number of predated seeds it is unlikely to reduce population sizes or curb the spread of the invasive alien tree in South Africa.